Breast cancer detection using flanged parallel-plate waveguide probe - Lee, Wilman Wei Jian. (2010)
Breast cancer has always been a major health concern to the general women population. Although conventional breast cancer imaging techniques are readily available, the inconsistencies, high false positive rates and soaring diagnosis fees of these practices have put them under scrutiny. Thus, the use of non-invasive alternative microwave imaging methodologies is proposed. Preliminary studies on these novel techniques have shown that these imaging methods provide a relatively high level of accuracy for detection of breast cancer. In this report, the experimental studies of breast cancer detection based on a proposed technique [1], which uses a flanged-parallel plate wave guide probe (PPWP) to analyze the complex permittivity contrast of cancer tumor in the form of S parameter measurements. Moreover, the development and characterization of broad band breast phantom materials were also performed and results have shown that phantoms with different levels of complex permittivity can be obtained by varying the oil content within the materials. In addition, validation of the proposed method [1] was carried out on the self fabricated breast mimicking phantom materials which simulate the different anatomy of a breast. Then, metal spheres and more challenging dielectric inclusions were fabricated and embedded within the phantoms as tumors. Subsequently, S parameters of tumor signatures were measured and analysis demonstrates that the size and location of the tumor can be estimated through the amplitude and frequency of the resonant response of the S parameters.